A new xanthid crab of the genus Medaeops Guinot, 1967, from Peninsular Malaysia, with a note on Leptodius granulosus Haswell, 1882 (Crustacea: Decapoda: Brachyura: Xanthidae) - Mendoza, Jose Christopher E.; Chong, V. C.; Ng, Peter K. L. (Zootaxa, 2009)
A new species of Medaeops Guinot, 1967, is described from the western coast of Selangor, Peninsular Malaysia. Medaeops potens new species, is only the second species of the genus known to occur in this region, and is most similar to another relatively common western Pacific species, M. granulosus (Haswell, 1882), particularly by having a cristate anterior margin on the merus of the ambulatory legs. It can easily be distinguished from M. granulosus and other congeners on the characters of the carapace, chelipeds, ambulatory legs and male gonopods. The taxonomy of Leptodius granulosus Haswell, 1882, is also stabilized by the assignment of a lectotype from the existing type material.